Effectiveness of Different Methods for Baroreflex Sensitivity Assessment in Determining the Severity of Cardiovascular Autonomic Neuropathy in Patients With Parkinson’s Disease - Huang, Chih-Cheng; Lai, Yun-Ru; Lien, Chia-Yi; Cheng, Ben-Chung; Kung, Chia-Te; Chiang, Yi-Fang; Lu, Cheng-Hsien (Frontiers in Neuroscience, 2022)
Background: Autonomic disorders are an important non-motor feature of Parkinson's disease (PD). Baroreflex sensitivity (BRS) is often used as an indicator of cardiovascular autonomic function, and it is clinically significant. Several different methods for BRS assessment have been described. We evaluated and compared the efficiency of several methods of BRS assessment for additional insight into the underlying physiology and the determination of its severity in patients with PD. Materials and Methods: Eighty-five patients with PD underwent cardiovascular autonomic testing. The Composite Autonomic Scoring Scale (CASS) was used to grade the severity of autonomic impairment and to define the presence of cardiovascular autonomic neuropathy (CAN). BRS was assessed using the Valsalva maneuver (BRS_VM). In addition, spontaneous BRS was computed using the sequence method and spectral method. Results and Conclusion: There was considerable agreement between the different methods of BRS assessment. Nevertheless, BRS_VM exhibited a higher degree of correlation with cardiovascular autonomic function than spontaneous BRS indexes obtained by sequence or spectral method. BRS_VM, rather than spontaneous BRS, also had a predictive value for the presence of CAN to diagnostic criteria by the CASS method in patients with PD.